Assessment of Chemically Treated Wood for Dimensional Stability , Strength Property and Termite Resistance - Deka, Manabendra; Saikia, C. N. (Indian Forester, 2004)
Experiments were conducted to assess the wood (Bombax ceiba Linn.) treated with thermosetting resins viz. Phenol Formaldehyde (PF) , Melamine Formaldehyde (MF) and Urea Formaldehyde (UF) and vinyl monomers viz. Acrylonitrile (AN) and Acrylamide (AA) for dimensional stabilization , strength and stiffness properties and termite (Odontotermis spp.) resistance. Dimensional stability in terms of antishrinking efficiency (ASE) was achieved 51.23-71.32% at 30.4-32.5 levels of weight per cent gain (WPG). After three cycles of repeated wetting and drying also , the treatments resulted bulking co-efficient (BC) of 9.52-14.14% and moisture excluding efficiency (MEE) of 30.20-42.25% of the wood at these levels of WPGs. The treated wood showed increase in modulus of rupture (MOR) by 7.33-21.01% and the stiffiness i.e. modulus of elasticity (MOE) by 6.96-12.12% of the treated wood over the untreated one with no remarkable effects on the specific gravity. The resin treated samples also showed resistant to termite attack even after one year of exposure to termite colony.